404 File not found a study on internet search engine preference - Turingan, Karl Ian S.
The aim of this thesis is to determine how a customer/internet user chooses an Internet Search Engine from the point of view of both customer and ISE. To do this, the study delved into what the customers/users saw as an ISE's best features. What customers saw as the most important factors that affect performance of ISEs were also looked into. Aside from these, the factors that motivated users to visit ISEs as well as their ritual/consummatory patterns of usage were taken into consideration to provide an even deeper perspective of how consumers choose an ISE. As another perspective, the viewpoint of ISE developers were also studied by way of a key informant interview. This approach provided new insight on the development, marketing and selling of ISE services to the different users/customers. The research is a descriptive study on how a customer chooses an Internet Search Engine (ISE). There were three methods used in the data gathering process. One hundred (100) ISE users were purposively selected as respondents. There were also five (5) users interviews. A key informant interview was also performed on an Internet Web Developer. From the data gathered it was found that ISE users look for convenience and speed of results for them to minimize their consumption of Internet online time, which is expensive here in the Philippines. It was also determined that developers on the other hand, look at accuracy of results as the most important feature of ISEs. Functionality and improvement of their main features is also what the developers look for.